APPLICATION OF THE BIOPHILIC CONCEPT TO KOLLEKTIV HOTEL BUILDINGS - Fajar, Arie Apriandi; Susilowati, Diana (ADBE, 2023)
The idea of architectural design with a biophilic approach is proven to be able to present a healthy space, reduce stress levels, and provide a sense of calm for humans who move in it. This is thanks to the design that connects nature and humans with the application of natural materials and natural analogy patterns into the design. Kollektiv Hotel located in the city of Bandung has biophilic design principles that deserve further research regarding how it is applied and its benefits. The purpose of this paper is to explain how a biophilic design concept is applied, the materials used, and the benefits of biophilic design concepts in hotel buildings. Data collection in this study uses qualitative methods, namely by surveying the research location, then collecting and analyzed with data obtained from electronic sources. The result of this study is that Kollektiv Hotel applies 10 of 14 biophilic design approaches to hotel buildings and restaurants, including about the visual relationship between the space formed with nature and also about the natural materials used and the meaning that arises from the use of biophilic design.